2012
DOI: 10.5194/tc-6-393-2012
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous detection of calving-related seismicity at Kronebreen, Svalbard

Abstract: Abstract. We detect and cluster waveforms of seismic signals recorded close to the calving front of Kronebreen, Svalbard, to identify glacier-related seismic events and to investigate their relation to calving processes. Single-channel geophone data recorded over several months in 2009 and 2010 are combined with eleven days of direct visual observations of the glacier front. We apply a processing scheme which combines conventional seismic event detection using a sensitive trigger algorithm and unsupervised clu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 53 publications
4
36
0
Order By: Relevance
“…Advances regularly occur in spring and summer when the velocity is especially high due to enhanced lubrication and calving rates are low (Köhler et al, 2012). The timely occurrence of the retreat in autumn is in line with observations from Köhler et al (2012), who found that in 2009 and 2010 calving-related seismicity at Kronebreen predominantly occurred in autumn, after the peak in velocity. In late summer and autumn decreased velocity and warm ocean water entering the fjord, hence increased melt, undercutting and calving, lead to retreat (Luckman et al, 2015).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Advances regularly occur in spring and summer when the velocity is especially high due to enhanced lubrication and calving rates are low (Köhler et al, 2012). The timely occurrence of the retreat in autumn is in line with observations from Köhler et al (2012), who found that in 2009 and 2010 calving-related seismicity at Kronebreen predominantly occurred in autumn, after the peak in velocity. In late summer and autumn decreased velocity and warm ocean water entering the fjord, hence increased melt, undercutting and calving, lead to retreat (Luckman et al, 2015).…”
Section: Discussionsupporting
confidence: 71%
“…Note that this thinning rate refers to fixed positions upstream of the front but not to the retreating front, the height of which above sea remained roughly constant. Kääb et al, 2005, Rolstad and Norland, 2009, Köhler et al, 2012, and Luckman et al, 2015.…”
Section: Kongsbreenmentioning
confidence: 99%
“…Kronebreen is currently in a period of rapid retreat, having receded ∼ 1 km between 2011 and 2016. Strong correlation between bulk calving rates and fjord water temperature indicates that this retreat primarily reflects melting of the glacier front beneath the waterline (Köhler et al, 2012;Luckman et al, 2015;.…”
Section: Study Areamentioning
confidence: 99%
“…This study builds on existing calving icequake research that has focused on the identification and location of calving events [ O'Neel et al , , ; Köhler et al , ]. Although iceberg sizes are potentially recoverable from glacial earthquake signals [ Tsai and Ekström , ; Veitch and Nettles , ], few other studies have systematically demonstrated an ability to capture iceberg size, and therefore calving flux, using properties of calving icequakes.…”
Section: Introductionmentioning
confidence: 99%